Corrosion and Hardness Study of Electroless Ni-P-ZnO Nano-Composite Coatings - Sharma, Neetu; Sharma, Sulaxna; Sharma, Kiran; Kalra, Gurmeet Singh; Sharma, Awanish (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00361);" role="presentation">In <span dir="ltr" style="left: calc(var(–scale-factor)*83.18px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908958);" role="presentation">current <span dir="ltr" style="left: calc(var(–scale-factor)*114.26px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934481);" role="presentation">investigation, <span dir="ltr" style="left: calc(var(–scale-factor)*171.38px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*193.61px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940467);" role="presentation">ZnO <span dir="ltr" style="left: calc(var(–scale-factor)*214.73px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*237.41px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906053);" role="presentation">composite <span dir="ltr" style="left: calc(var(–scale-factor)*281.45px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931187);" role="presentation">covering h<span dir="ltr" style="left: calc(var(–scale-factor)*324.31px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.801776);" role="presentation">as <span dir="ltr" style="left: calc(var(–scale-factor)*335.59px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">been <span dir="ltr" style="left: calc(var(–scale-factor)*357.31px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897197);" role="presentation">urbanized <span dir="ltr" style="left: calc(var(–scale-factor)*399.55px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*412.39px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96227);" role="presentation">exterior of MS <span dir="ltr" style="left: calc(var(–scale-factor)*475.06px); top: calc(var(–scale-factor)*379.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891573);" role="presentation">substrate by <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0021);" role="presentation">EL <span dir="ltr" style="left: calc(var(–scale-factor)*87.62px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891649);" role="presentation">procedure<span dir="ltr" style="left: calc(var(–scale-factor)*127.70px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944226);" role="presentation">. The <span dir="ltr" style="left: calc(var(–scale-factor)*152.66px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905551);" role="presentation">next <span dir="ltr" style="left: calc(var(–scale-factor)*173.18px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.836607);" role="presentation">stage Z<span dir="ltr" style="left: calc(var(–scale-factor)*203.21px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911296);" role="presentation">nO <span dir="ltr" style="left: calc(var(–scale-factor)*218.93px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869253);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*241.61px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922739);" role="presentation">particles were <span dir="ltr" style="left: calc(var(–scale-factor)*301.85px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883524);" role="presentation">synthesized, <span dir="ltr" style="left: calc(var(–scale-factor)*354.43px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*365.71px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947558);" role="presentation">add in <span dir="ltr" style="left: calc(var(–scale-factor)*394.87px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96065);" role="presentation">into <span dir="ltr" style="left: calc(var(–scale-factor)*413.83px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04836);" role="presentation">EL Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*442.66px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931806);" role="presentation">P medium<span dir="ltr" style="left: calc(var(–scale-factor)*484.42px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00187);" role="presentation">. 5 gpl <span dir="ltr" style="left: calc(var(–scale-factor)*515.14px); top: calc(var(–scale-factor)*392.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940467);" role="presentation">ZnO <span dir="ltr" style="left: calc(var(–scale-factor)*94.58px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano-<span dir="ltr" style="left: calc(var(–scale-factor)*117.26px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936354);" role="presentation">particles were <span dir="ltr" style="left: calc(var(–scale-factor)*179.18px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901949);" role="presentation">supplementary <span dir="ltr" style="left: calc(var(–scale-factor)*242.45px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*254.57px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P <span dir="ltr" style="left: calc(var(–scale-factor)*277.73px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936929);" role="presentation">acidic <span dir="ltr" style="left: calc(var(–scale-factor)*305.93px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964371);" role="presentation">unit <span dir="ltr" style="left: calc(var(–scale-factor)*325.75px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01638);" role="presentation">for co-<span dir="ltr" style="left: calc(var(–scale-factor)*354.43px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917478);" role="presentation">deposition. <span dir="ltr" style="left: calc(var(–scale-factor)*402.91px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*422.83px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.854228);" role="presentation">heat <span dir="ltr" style="left: calc(var(–scale-factor)*443.86px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917448);" role="presentation">management of <span dir="ltr" style="left: calc(var(–scale-factor)*511.66px); top: calc(var(–scale-factor)*405.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.79035);" role="presentation">as- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87612);" role="presentation">prepared <span dir="ltr" style="left: calc(var(–scale-factor)*110.90px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-<span dir="ltr" style="left: calc(var(–scale-factor)*124.10px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">P/<span dir="ltr" style="left: calc(var(–scale-factor)*132.50px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*154.70px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934811);" role="presentation">ZnO <span dir="ltr" style="left: calc(var(–scale-factor)*176.66px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01154);" role="presentation">EL <span dir="ltr" style="left: calc(var(–scale-factor)*192.77px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928812);" role="presentation">outside layer <span dir="ltr" style="left: calc(var(–scale-factor)*249.29px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868899);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*268.49px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872653);" role="presentation">conceded <span dir="ltr" style="left: calc(var(–scale-factor)*310.13px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947658);" role="presentation">out at <span dir="ltr" style="left: calc(var(–scale-factor)*337.63px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906137);" role="presentation">380<span dir="ltr" style="left: calc(var(–scale-factor)*356.35px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06275);" role="presentation">C in Ar<span dir="ltr" style="left: calc(var(–scale-factor)*388.75px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898318);" role="presentation">gon <span dir="ltr" style="left: calc(var(–scale-factor)*407.47px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987186);" role="presentation">for 1h. <span dir="ltr" style="left: calc(var(–scale-factor)*439.15px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The<span dir="ltr" style="left: calc(var(–scale-factor)*454.78px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.785388);" role="presentation">se <span dir="ltr" style="left: calc(var(–scale-factor)*466.90px); top: calc(var(–scale-factor)*419.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916916);" role="presentation">coatings were <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93617);" role="presentation">analysed for <span dir="ltr" style="left: calc(var(–scale-factor)*127.22px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935975);" role="presentation">surface mor<span dir="ltr" style="left: calc(var(–scale-factor)*176.54px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945856);" role="presentation">phology, elemental composition and phase <span dir="ltr" style="left: calc(var(–scale-factor)*358.99px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897452);" role="presentation">analysis <span dir="ltr" style="left: calc(var(–scale-factor)*395.59px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963878);" role="presentation">by <span dir="ltr" style="left: calc(var(–scale-factor)*409.87px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939957);" role="presentation">FESEM<span dir="ltr" style="left: calc(var(–scale-factor)*442.18px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05366);" role="presentation">, EDAX, <span dir="ltr" style="left: calc(var(–scale-factor)*483.46px); top: calc(var(–scale-factor)*433.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985155);" role="presentation">and XRD <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891639);" role="presentation">analysis. C<span dir="ltr" style="left: calc(var(–scale-factor)*117.62px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927091);" role="presentation">orrosion <span dir="ltr" style="left: calc(var(–scale-factor)*155.30px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92935);" role="presentation">resistance quality <span dir="ltr" style="left: calc(var(–scale-factor)*231.05px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952854);" role="presentation">of depositions was <span dir="ltr" style="left: calc(var(–scale-factor)*313.63px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872653);" role="presentation">conceded <span dir="ltr" style="left: calc(var(–scale-factor)*355.75px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918334);" role="presentation">out <span dir="ltr" style="left: calc(var(–scale-factor)*372.79px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99871);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*384.79px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00481);" role="presentation">5 % NaCl solution <span dir="ltr" style="left: calc(var(–scale-factor)*468.70px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962863);" role="presentation">by <span dir="ltr" style="left: calc(var(–scale-factor)*482.98px); top: calc(var(–scale-factor)*446.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974655);" role="presentation">long term <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927923);" role="presentation">immersion <span dir="ltr" style="left: calc(var(–scale-factor)*118.34px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910305);" role="presentation">experiment. <span dir="ltr" style="left: calc(var(–scale-factor)*169.46px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927168);" role="presentation">Hardness is measured by micro-<span dir="ltr" style="left: calc(var(–scale-factor)*302.81px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884163);" role="presentation">hardness tester. A <span dir="ltr" style="left: calc(var(–scale-factor)*379.99px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890737);" role="presentation">consistent <span dir="ltr" style="left: calc(var(–scale-factor)*423.55px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941324);" role="presentation">allocation <span dir="ltr" style="left: calc(var(–scale-factor)*466.78px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.991421);" role="presentation">of ZnO <span dir="ltr" style="left: calc(var(–scale-factor)*500.62px); top: calc(var(–scale-factor)*459.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874197);" role="presentation">nano- <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912485);" role="presentation">particles <span dir="ltr" style="left: calc(var(–scale-factor)*112.79px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*127.46px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00091);" role="presentation">EL <span dir="ltr" style="left: calc(var(–scale-factor)*146.54px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06052);" role="presentation">Ni-P <span dir="ltr" style="left: calc(var(–scale-factor)*172.44px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922347);" role="presentation">medium <span dir="ltr" style="left: calc(var(–scale-factor)*211.97px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937819);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*225.65px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939403);" role="presentation">long-<span dir="ltr" style="left: calc(var(–scale-factor)*246.65px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881358);" role="presentation">established <span dir="ltr" style="left: calc(var(–scale-factor)*298.08px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951502);" role="presentation">by <span dir="ltr" style="left: calc(var(–scale-factor)*314.95px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941189);" role="presentation">FESEM/<span dir="ltr" style="left: calc(var(–scale-factor)*349.87px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02135);" role="presentation">EDAX <span dir="ltr" style="left: calc(var(–scale-factor)*384.55px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888389);" role="presentation">results. <span dir="ltr" style="left: calc(var(–scale-factor)*420.07px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928416);" role="presentation">Corrosion <span dir="ltr" style="left: calc(var(–scale-factor)*467.05px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*488.40px); top: calc(var(–scale-factor)*472.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.84993);" role="presentation">hardness <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940965);" role="presentation">examinations put forward <span dir="ltr" style="left: calc(var(–scale-factor)*180.50px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902513);" role="presentation">that <span dir="ltr" style="left: calc(var(–scale-factor)*199.13px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00091);" role="presentation">EL Ni-P-<span dir="ltr" style="left: calc(var(–scale-factor)*237.17px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940467);" role="presentation">ZnO <span dir="ltr" style="left: calc(var(–scale-factor)*259.01px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8964);" role="presentation">coatings <span dir="ltr" style="left: calc(var(–scale-factor)*295.97px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943098);" role="presentation">illustrate <span dir="ltr" style="left: calc(var(–scale-factor)*334.63px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908272);" role="presentation">superior <span dir="ltr" style="left: calc(var(–scale-factor)*370.99px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899481);" role="presentation">performance <span dir="ltr" style="left: calc(var(–scale-factor)*424.99px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.788658);" role="presentation">as <span dir="ltr" style="left: calc(var(–scale-factor)*436.99px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909356);" role="presentation">judge <span dir="ltr" style="left: calc(var(–scale-factor)*462.82px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*474.22px); top: calc(var(–scale-factor)*486.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978002);" role="presentation">simple Ni-P <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*499.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902508);" role="presentation">depositions.